Embolisasi Trans Arterial Pra Operasi pada Metastatic Bone Disease dari Renal Cell Carcinoma - Rizqi, Putri; Setyawan, Agung; Achmad; Aslam, Achmad (RSUD Dr. Saiful Anwar Province of East Java, 2022)
Metastasis has been literally defined as the spread of cancer from the main body part when the cancer starts to induce other parts of the body. Approximately, one third of patients with advanced renal cell carcinoma (RCC) have presented bone metastases which are often osteolytic causing substantial morbidity, such as: pain pathological fractures, spinal cord compression and hypercalcemia. Additionally, the presence of bone metastases in RCC is also associated with a poor prognosis. This paper reports a case presentation regarding embolization in a case of a 25-year-old female patient with a pathological diagnosis of a pathological fracture at the L1 level dt MBD Process Renal Cell Carcinoma prior to spinal stabilization surgery. Embolization hence plays an important role in treating hypervascular bone metastases, providing effective means of treating hemorrhagic conditions by minimizing the bleeding supply to tumor masses. In sum, embolization could be performed either as a definitive treatment or as an adjunct to subsequent surgical management.